Certain integral operator and strongly starlike functions. (30th May 2002) - Liu, Jin-Lin
Abstract : LetS ∗ ( ρ, γ ) denote the class of strongly starlike functions of orderρ and typeγ and letC ( ρ, γ ) be the class of strongly convex functions of orderρ and typeγ . By making use of an integral operator defined by Jung et al. (1993), we introduce two novel families of strongly starlike functionsS β α ( ρ, γ ) andC β α ( ρ, γ ) . Some properties of these classes are discussed.